Reentrant strain glass transition in Ti-Ni-Cu shape memory alloy. (March 2022) - Wang, Wenjia; Ji, Yuanchao; Fang, Minxia; Wang, Dong; Ren, Shuai; Otsuka, Kazuhiro; Wang, Yunzhi; Ren, Xiaobing
Abstract: Reentrant glass transition, referring to a reversible transition from a high-temperature ordered phase to a low-temperature glassy phase, is unusual and difficult to be understood, because at low temperature the glassy phase is usually less thermodynamically stable than the ordered phase. In this work, we report a systematic study of a reentrant strain glass (RSTG) transition between a strain-ordered martensitic phase and a strain glass in a Ti50 Ni34 Cu16 shape memory alloy. This transition is characterized by a temperature invariance of average B19 martensitic structure, a deviation in heat flow and resistivity curves, a frequency-dependent behavior of storage modulus and internal friction curves, and a peak in a zero-field cooling curve. In-situ microstructural observations show that the B19 martensitic domain pattern keeps unchanged upon cooling while nanodomains with local 4H symmetry gradually emerge and grow in large martensitic domains. Moreover, the RSTG transition exhibits low modulus (∼24 GPa) and high damping (tan δ > 0.075) over a large temperature range. Based on experimental results, we established a new Ti50 Ni50-x Cux phase diagram with the RSTG state included. This phase diagram helps understand the abnormal formation of RSTG: since Cu dopants stabilize the B19 phase instead of B19' phase, with sufficient Cu dopants ( x = 16) the B19-B19' transition is thermodynamically suppressed and the RSTG transition appears, which resembles the conventional strain glass formation in a Ti50-x Ni50+ x phase diagram. The microstructural evolution of RSTG with nanodomains embedded in large domains explains novel properties and puzzles in Ti-Ni-Cu alloys. We further predict more unusual properties could be found in RSTG materials. Graphical abstract: Image, graphical abstract